Occupational Safety Risks of Online Motorcycle Taxi Drivers: Case Study and OSH Recommendations - Winata, Rivaldi Andika; Budiman, Ridho Dedy Arief (Journal of Multidiscipline and Collaboration Research, 2025)
Online motorcycle taxi (ojol) drivers are part of the rapidly growing informal sector within the digital economy but continue to face high occupational safety and health (OSH) risks without adequate protection. This study aims to analyze the level of occupational safety risk among ojol drivers and formulate relevant OSH policy recommendations for the non-formal sector. The research employed a quantitative descriptive approach involving 100 ojol drivers in Pontianak City. Data were collected through questionnaires and structured interviews and analyzed using descriptive statistics. The results show that 65% of workers experience work fatigue, 42% have been involved in minor accidents, and 18% have suffered moderate to severe accidents. The main risk factors include long working hours, pressure from incentive systems, and congested traffic conditions. These findings indicate the urgent need for OSH policies that encompass the non-formal, platform-based sector. The study contributes theoretically to the development of adaptive OSH models in the era of the gig economy while offering practical recommendations for both government and platform providers to enhance occupational safety and improve the well-being of ojol drivers.